Specifying and Analyzing a Software Testing Ontology at the Top-Domain Ontological Level - Tebes, Guido (2021)
One of the Software Engineering areas that supports quality assurance is testing. Given that specific processes, artefacts, methods and ultimately strategies for software testing involve a large number of domain concepts, it is valuable to have a robust conceptual base, that is. a software testing ontology that defines the terms, properties, relationships and axioms explicitly and unambiguously. Ontologies for instance foster a clearer terminological understanding of process and method specifications for strategies, among many other benefits. After analyzing both the results of a conducted Systematic Literature Review of primary studies on conceptualized software testing ontologies and the state-of-the-art of testing-related standards, we decided to develop a software testing top-domain ontology named TestTDO that fits our goals. Therefore, this article specifies development, verification and validation aspects of the TestTDO. which was built following the Design Science Research approach.